COVID-19 pneumonia: prediction of patient outcome by CT-based quantitative lung parenchyma analysis combined with laboratory parameters - Do, Thuy; Skornitzke, Stephan; Merle, Uta; Kittel, Maximilian; Hofbaur, Stefan; Melzig, Claudius; Kauczor, Hans-Ulrich; Wielpütz, Mark Oliver; Weinheimer, Oliver (PLOS ONE, 2022)
To evaluate the prognostic value of fully automatic lung quantification based on spectral computed tomography (CT) and laboratory parameters for combined outcome prediction in COVID-19 pneumonia.